The Epidemiology of Sepsis during Rapid Response Team Reviews in a Teaching Hospital. Issue 2 (March 2015) - Cross, G.; Bilgrami, I.; Eastwood, G.; Johnson, P.; Howden, B. P.; Bellomo, R.; Jones, D.
In a three-month retrospective study, we assessed the proportion of rapid response team (RRT) calls associated with systemic inflammatory response syndrome (SIRS) and sepsis. We also documented the site of infection (whether it was community- or hospital-acquired), antibiotic modifications after the call and in-hospital outcomes. Amongst 358 RRT calls, two or more SIRS criteria were present in 277 (77.4%). Amongst the 277 RRT calls with SIRS criteria, 159 (57.4%) fulfilled sepsis criteria in the 24 hours before and 12 hours after the call. There were 118 of 277 (42.6%) calls with SIRS criteria but no evidence of sepsis and 62 of 277 (22.3%) calls associated with both criteria for sepsis as well as an alternative cause for SIRS. Hence, 159 (44.4%) of all 358 RRT calls over the three-month study period fulfilled criteria for sepsis and in 97 (159–62) (27.1%) of the 358 calls, there were criteria for sepsis without other causes for SIRS criteria. The most common sites of infection were respiratory tract (86), abdominal cavity (38), urinary tract (26) and bloodstream (26). Infection was hospital-acquired in 91 (57.2%) and community-acquired in 67 (42.1%) cases, respectively. Patients were on antibiotics in 127 of 159 (79.9%) cases before the RRT call and antibiotics were added or modified in 76 of 159 (47.8%) cases after RRT review. The hospital length-of-stay of patients who received an RRT call associated with sepsis was longer than those who did not (16.0 [8.0 to 28.5] versus 10 [6.0 to 18.0]; P =0.002).